Quality provision and reporting when health care services are multi-dimensional and quality signals imperfect - Katharina Huesmann; Wanda Mimra (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We model competition for a multi-attribute service, like health care services, where consumers observe attribute quality imprecisely before deciding on a provider. High quality in one attribute is more important in terms of ex post utility. Attribute quality is stochastic, providers can shift resources in order to increase expected quality in some attributes. Consumers rationally focus on attributes depending on signal precision and beliefs about the providers' resource allocations. When signal precision is such that consumers focus weakly on the less important attribute, any Perfect Bayesian Nash Equilibrium is inefficient. Increasing signal precision can reduce welfare, as the positive effect of better provider selection is overcompensated by the negative effect that a shift in consumer focusing has on provider quality choice. We discuss the providers' incentives for information disclosure.
Keywords: L15; D83; I11; 330